Scientific Opinion on the safety assessment of the substance fatty acids, C16‐18 saturated, hexaesters with dipentaerythritol for use in food contact materials. (18th February 2015) - ,; ,
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety assessment of fatty acids, C16‐18 saturated, hexaesters with dipentaerythritol (FADP), FCM substance No 01053, for use as a processing agent at up to 1.5 % in various types of plastics. Based on the modelled specific migration calculation results, it cannot be ruled out that the overall migration limit may be exceeded. No toxicological data were provided for the assessed substance. Toxicological data from similar pentaerythritol fatty acids were submitted for "read across". Based on the genotoxicity data provided, the CEF Panel considered that there is no indication of mutagenic potential of the substance. The CEF Panel concluded that the substance FADP is not of safety concern for the consumer if used in polymers intended for contact with all types of foodstuffs at all time–temperature conditions, provided that the fatty acid precursors are obtained from edible fats or oils and that any impurities in the dipentaerythritol are under the control of the producer.